2015
DOI: 10.1093/jamia/ocv082
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the use of a mHealth medication adherence promotion intervention for low-income adults with type 2 diabetes

Abstract: Racial/ethnic minorities, older adults, and persons with lower health literacy or more depressive symptoms appeared to be the least engaged in a mHealth intervention. To facilitate equitable intervention impact, future research should identify and address factors interfering with mHealth engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 35 publications
4
110
1
Order By: Relevance
“…19 Table 2 reports these characteristics by participants who did and did not complete a follow-up interview. Of the 60 participants who completed the interview, the average age was 50.0 -10.1 years old; 65% were female and 62% were non-white (95% African-American); 15% had less than a high school degree or equivalent; 70% had annual household incomes less than $20K; and 83% were either uninsured or had public insurance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Table 2 reports these characteristics by participants who did and did not complete a follow-up interview. Of the 60 participants who completed the interview, the average age was 50.0 -10.1 years old; 65% were female and 62% were non-white (95% African-American); 15% had less than a high school degree or equivalent; 70% had annual household incomes less than $20K; and 83% were either uninsured or had public insurance.…”
Section: Resultsmentioning
confidence: 99%
“…17,19 Users receive a daily tailored text message at a random time each day addressing 1 of their 3 highest ranked barriers to adherence (out of 17 assessed). Barriers are reassessed monthly to update the user experience.…”
Section: Med Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although minorities are disproportionately likely to own a smartphone [14] and to have chronic conditions requiring care coordination [24,25], past research has found that racial/ethnic minorities had lower uptake of technologies such as patient portals [26,27] or a longitudinal mHealth intervention with daily text messaging [28]. In contrast, high-risk FQHC patients in this study expressed a willingness to use the proposed app, which leverages automated location tracking technologies in a way that could enhance information transfer to PCPs, while requiring minimal human effort from app users.…”
Section: Discussionmentioning
confidence: 99%
“…The MED intervention uses the SuperEgo mobile communications platform (Mulvaney et al, 2012) to deliver and tailor text messages and voice communications to promote medication adherence (Nelson et al, 2015; Osborn & Mulvaney, 2013). MED addresses users’ unique barriers to adherence.…”
Section: Methodsmentioning
confidence: 99%